Bainite transformation in Fe-C alloys (2005)
Some Fe-C alloys have an excellent combination of toughness and mechanical strength, associated with the products of the bainitic reaction, which makes them useful in the manufacture of machine components under high stress. However, in our environment the knowledge of this transformation is reduced; This makes the competitiveness of the metalworking sector in the globalized economy difficult. In this work a compendium of the basic concepts of the bainitic reaction is made, which goes beyond the classical texts of metal phase transformations and considering the latest advances that have been made in their study. In addition, the most important factors of bainite in both steels and nodular smelters are analyzed. The transformation mechanisms, reaction kinetics, microstructural characteristics and mechanical properties are discussed. The objective of the work is to spread the notions and techniques required for the implementation of this phase transformation, seeking to promote the development of bainitic products.